Physical oceanography during the cruise SO269 in South China Sea in September 2019, station SO269_180-2-18 (SCS19_18) - Joanna J Waniek; Helena C Frazão; Ralf D Prien; Siegfried Krüger; Ingo Schuffenhauer; Robert Mars (PANGAEA, 2021)
This dataset provides 131 CTD profiles measured on board of the German R/V Sonne (cruise SO269) in the northern South China Sea, under the project SOCLIS – South China Sea Natural Laboratory under Climatic and Anthropogenic Stress, in August and September 2019. The 131 profiles of temperature, salinity, dissolved oxygen, fluorescence, turbidity, surface irradiance (SPAR) and Photosynthetically active radiation (PAR), and sound velocity were measured using a CTD Sea-Bird SBE 911 plus, together with oxygen sensor (SBE 43), PAR sensor (Biospherical, QCP-2350 + QSR-2200), and a fluorometer (WET Labs ECO-FLNTU(RT)D). Additionally, oxygen saturation, potential temperature and sigma-theta (with reference to the surface) were calculated. The 131 CTD profiles are distributed by 81 stations and aim to study the impact of a growing anthropogenic pressure around the Pearl River Estuary into the northern shelf of the South China Sea towards the deep sea. The dataset was used to study the presence and spatial distribution of natural and synthetic estrogenic compounds and pharmaceutical and personal care products (PPCPs) in the Pearl River Estuary and northern shelf of the South China Sea.
In: Waniek, JJ et al. (2021): Physical oceanography during the cruise SO269 in South China Sea in August/September 2019 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.938934